Curved Path Following Control for a Small Fixed-Wing UAV with Parameters Adaptation - Yang Chen; Nan Li; Wei Zeng; Yongliang Wu (Applied Sciences, 2022)
This paper presents an approach to address the curved-path following problem of a fixed-wing UAV, which can reach uniform optimal path-following performance for different initial states and control processes. First, a proper guidance law is designed following a class of horizontal smooth paths with fixed control parameters. The stability of the relative nonlinear system is guaranteed by the Lyapunov stability theory. The influence of the control parameters on path-following performance has been analyzed. Second, the rules of the time-varying control parameters are designed separately. The rules of the time-varying P-like parameter are designed by analyzing the dynamic characteristics of the nonlinear system with different initial flight states. The rules of the time-varying D-like parameter are designed based on the fuzzy logic technique. The stability of the corresponding nonautonomous nonlinear system is also proved. The simulations are carried out in the Matlab/Simulink environment with an Aerosonde UAV model. The results are presented to illustrate the effectiveness and high path-following performances of the proposed control strategies.